Peran Pengawas dalam Merekonstruksi Pendidikan Islam - Harinurdi (Tarbiyah Departement collaboration with AMCA, 2016)
Islamic education is a comprehensive educational and integrative. All the components required to perform its role of Islamic education Islamic education in order to be successful. An Islamic education supervisors to perform its role to the starting point in Islamic values. In the implementation, there are several techniques of Islamic education supervisors who do supervisors. Supervisory duties fostering Islamic education teachers to be able to have a religious type of integration, by modeling or by uswah hasanah, so teachers are also imitating doing the same thing. Supervisors are able to perform its role is always to know and monitor the conditions and the competence of teachers who supervised.